2015
DOI: 10.1039/c5cp00012b
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric interface modifiers in hybrid polymer solar cell prototypes investigated by fluorescence voltage spectroscopy

Abstract: Carboxylated oligothiophenes were evaluated as interfacial modifiers between the organic poly(3-hexylthiophene) (P3HT) and inorganic TiO2 layers in bilayer hybrid polymer solar cells. Carboxylated oligothiophenes can be isolated using conventional purification techniques resulting in pure, monodisperse molecules with 100% carboxylation. Device prototypes using carboxylated oligothiophenes as interfacial modifiers showed improved performance in the open-circuit voltage and fill factor over devices using unmodif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These dyes are metal ion-free dyes and have an electron-rich thiophene group. It was found that the dyes improve the V OC due to a dipole moment at the interface [16,28]. Oligothiophenes are discrete, monodisperse molecules, and are distinct from polythiophene, which inherently exists as a distribution of molecular weights.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These dyes are metal ion-free dyes and have an electron-rich thiophene group. It was found that the dyes improve the V OC due to a dipole moment at the interface [16,28]. Oligothiophenes are discrete, monodisperse molecules, and are distinct from polythiophene, which inherently exists as a distribution of molecular weights.…”
Section: Introductionmentioning
confidence: 99%
“…Oligothiophenes are discrete, monodisperse molecules, and are distinct from polythiophene, which inherently exists as a distribution of molecular weights. A pure carboxylated oligothiophene can be isolated from any unfunctionalized oligomers via column chromatography and recrystallization [28]. Such organic semiconducting oligothiophenes have been intensively investigated and widely used in organic photovoltaic (OPVs) due to the presence of excellent charge transport properties and tunable optical/electrochemical properties [29].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 a further shows that the insertion of 4T dye at the TiO 2 /P3HT and TiO 2 /doped P3HT interface resulted in a high open-circuit voltage around 0.87 V which is consistent with our previous work 31 . This is probably due to the increased number of electron-rich thiophene units present with 4T dye treated TiO 2 /P3HT and TiO 2 /doped P3HT nanocomposites, which leads to a dipole moment at the interface 30 , 33 , 47 . Furthermore, the current density of 4T dye treated devices with both doped Spiro-OMeTAD and doped P3HT were around 6.43 mA/cm 2 and 13.02 mA/cm 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the insertion of quaterthiophene based 4T dye at Titanium dioxide/Poly (3-hexylthiophene) interface showed an enhanced efficiency 22 , 30 and, improved hole mobility of the polymer nanocomposite by up to two orders of magnitude compared to the corresponding control 31 . This electron-rich thiophene cyanoacrylic acid group containing metal-free dye led to devices with high via generation of dipole moments at the interface 30 , 32 , 33 . Molar extinction coefficient ( ε ) of 4T dye is also higher compared to commercial ruthenium based N719 and Z907 dyes 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Presence of strong electron withdrawing -CN moiety neighboring to the -COOH anchoring group facilitates a molecular dipole directing away from the TiO 2 surface, and enhances the electron affinity of the molecules, simultaneously enhances the J sc and V oc 2.87 [86] TiO 2 /carboxylated oligothiophene/P3HT Addition of carboxylated oligothiophenes enhanced surface coverage and improved interfacial interactions. 0.11 [87] TiO 2 /Z907/P3HT/PEDOT:PSS…”
mentioning
confidence: 99%